The Impact of Excise Tax Increases on Ethyl Alcohol Sales in Lithuania - Bartkus, Algirdas (Ekonomika, 2020)
This article provides empirical evidence that the demand for ethyl alcohol in Lithuania is price elastic and the root cause of this elasticity is the competition between Lithuanian and Polish sellers. The basis for the emergence of competition lies in the price differences between the countries, which arise as a direct consequence of the Lithuanian government’s policy in the alcohol sector, which is directed towards reckless increases in excise duties. The increase in Lithuanian excise duties leads to a wider price gap between countries and in the first months after the increase results increases in prices. In subsequent months, Lithuanian importers and manufacturers tend to revise the assortment and costs, replacing more expensive goods with cheaper ones or slightly alter the markups. These changes are the main reason why demand in the domestic market gradually recovers. The price elasticity of demand predetermines the gradual recovery of the ethyl alcohol market, but each increase in excise duty reduces the manufacturers’ markups and (or) leads to the changes in product range, where higher-costs products are displaced by lower-cost products.